Aerobic Endurance and Heart Pulse Rate among Male Undergraduate in Iraq after 8-Weeks Speed Play (fartlek) Intervention Program - Husam Juma Rachid Al-Rubaie (Journal of Global Pharma Technology, 2016)
This study aims to investigate whether 8-weeks (fartlek) intervention program could improve aerobic endurance and heart pulse rate to enhance the level of fitness for sedentary male students in Iraq. An 8-weeks (fartlek) intervention program depends on outdoor physical activities.44 sedentary undergraduate male students from Al-Mustansiriya University dorms. Were divided by two groups experimental and control group (n=22 in each group) completed practical tests at pre-test and post-test. The subjects of the groups were tested on 1500m run/walk to measure the aerobic endurance, the heart pulse rate measured at 3 times 1-min before, 1 and 3-min after. The collected data were analyzed statistically though analysis of t-test to find out the significant differences. The results showed that the (fartlek) exercises can positively influence the fitness of the sedentary male students.From the previous findings we can conclude the following conclusions:Fartlek training could be very useful method to develop the fitness variable of Aerobic Endurance.Fartlek training could be very useful method to develop the functional capability which is represented by heart plus rate level (before the effort and after the effort by one and three minute).Keywords: Fartlek, Aerobic Endurance, Heart pulse rate, sedentary undergraduate male students.